Metformin alleviates irradiation-induced intestinal injury by activation of FXR in intestinal epithelia - Yang, Jing-Yu; Liu, Meng-Jie; Lv, Lin; Guo, Jin-Rong; He, Kai-Yue; Zhang, Hong; Wang, Ke-Ke; Cui, Cui-Yun; Yan, Bei-Zhan; Du, Dan-Dan; Wang, Jin-Hua; Ding, Qiang; et al. (Frontiers in Microbiology, 2022)
Abdominal irradiation (IR) destroys intestinal mucosal barrier, leading to severe intestinal infection and multiple organ dysfunction syndrome. There is an urgent need to find safe and effective treatments to reduce IR-induced intestinal injury. Herein, we reported that metformin protected mice from abdominal IR-induced intestinal injury by improving the composition and diversity of intestinal flora. Elimination of intestinal microbiota (Abx) abrogated the protective effects of metformin on irradiated mice. We further characterized that treatment of metformin increased murine intestinal abundance of Lactobacillus, which mediated the radioprotective effect. Administration of Lactobacillus or fecal microbiota transplantation (FMT) into Abx mice considerably lessened IR-induced intestinal damage and restored the radioprotective function of metformin in Abx mice. In addition, applying murine intestinal organoid model, we demonstrated that IR inhibited the formation of intestinal organoids, and metformin alone bore no protective effect on the organoids after IR. However, combination of metformin and Lactobacillus or Lactobacillus alone displayed a strong radioprotection on organoid formation. We demonstrated that metformin / Lactobacillus activated the farnesoid X receptor (FXR) signaling in intestinal epithelial cells and hence upregulated tight junction proteins and mucins in intestinal epithelia, increased the number of goblet cells, and augmented the mucus layer thickness to maintain the integrity of intestinal epithelial barrier, which eventually contributed to reduced radiation intestinal injury. In addition, we found that Lactobacillus abundance was significantly increased in the intestine of patients receiving metformin while undergone abdominal radiotherapy and the abundance was negatively correlated with the diarrhea duration of patients. In conclusion, our results demonstrate that metformin possesses a protective effect on IR-induced intestinal injury by upregulating the abundance of Lactobacillus in the intestine.